Revisión del género crenea aublet (litraceas) (1986)
The taxonomical revision of the genus Crenea shows that there are only two species. Descriptions, keys, illustrations and distribution map are given. Pollens are neatly different. Affinities of Crenea with Verrutricolporites rotundiporus (fossil) are commented.